ANALISIS PENGGUNAAN UANG ELEKTRONIK (Studi Kasus Pada Mahasiswa Pengguna Produk Flazz BCA di Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Candraditya, Habsari; Idris, Idris (Diponegoro Journal of Management, 2013)
This study aimed to analyze the interest of students to use the Flazz BCA card not only as identity card but also as a means of payment for economic transactions. Flazz BCA card at this time has been developed to become multifunctional card, card that is not only can serve as a means of electronic payments but also can be used as an identity card. The functions began to be implemented in the Faculty of Economics and Business, University of Diponegoro since mid-2012.The purpose of this study is to examine the effects of independent variable such as product knowledge, perceived of usefulness, and suitability price against to intention to use as dependent variable.This study was conducted at the The Faculty of Economics and Business University of Diponegoro students with a total sample of 125 respondents drawn using purposive sampling technique. Data processing is done by using analysis data includes the validity test, reliability test, normality test, multicolinearity test, heteroscedasticity test, linear regression analysis, F-test, t-test, and coefficient of determination test.The results of this study indicate that all variables have a positive coefficient values, but not all independent variables have a significant effect on the dependent variable. Suitability price has the greatest influence on intention to use because it has the largest regression coefficient 0.368. Perceived of usefulness has the second greatest influence on intention to use since it has regression coefficient 0.262. Meanwhile product knowledge has the smallest impact because it has the smallest value of the regression coefficient 0.105. Results showed that the coefficient of determination (adjusted R square) of the independent variables in this study were able to explain 31.6% of intention to use multifunction card Flazz BCA as a means of payment that has been used as identity cards among students of The Faculty of Economics and Business University of Diponegoro. While the remaining 68.4% is explained by other variables which is not included in this study.